Phenomenology Study: Developing Intrapersonal Intelligence Through Multicultural Values In Early Childhood At Yos Sudarso Kindergarten In Purwakarta Regency - Wulandari, Hayani; Nikawanti, Gia; Muqodas, Idat (International Conference on Elementary Education, 2020)
This study aims to determine and understand the role and function of multicultural education in developing intrapersonal intelligence in early childhood and to share insights with the public about how to instill multicultural education early on in children. This research will be carried out for 6 months from April to October 2019. The place of the research is located at Yos Sudarso kindergarten in Purwakarta Regency. This research uses a qualitative method with a phenomenological research design. Phenomenology research in the sense of research is focused on one phenomenon that is chosen and wants to be understood in-depth, namely how the role and function of multicultural education in developing intrapersonal intelligence in early childhood in Yos Sudarso kindergarten. The data analysis technique in this study uses data reduction, which actually encodes and classifies data according to the research indicators. The results of this study are the role and function of multicultural education in developing intrapersonal intelligence in early childhood in Yos Sudarso kindergarten. This can be seen from the behavior of children who have consistently shown multicultural behavior in teaching and learning activities in the classroom